The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.21037/jtd.2018.03.126
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to predict lymph node metastasis in solid lung adenocarcinoma: a radiomics nomogram

Abstract: The radiomics nomogram, based on preoperative CT images, can be used as a noninvasive method to predict LNM in patients with solid lung adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 33 publications
1
65
0
Order By: Relevance
“…(6) The ROI included bronchi, blood vessels, and vacuoles within the nodules, excluding normal lung tissue. Previous studies [16][17][18] had reported that the radiomic analyses were capable of predicting the LNM in the patients with lung adenocarcinoma. The predicative AUC values based on the radiomic analyses regarding the patients who had both pre-surgical node-positive and node-negative in the CT scans were 0.86 from 159 patients [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(6) The ROI included bronchi, blood vessels, and vacuoles within the nodules, excluding normal lung tissue. Previous studies [16][17][18] had reported that the radiomic analyses were capable of predicting the LNM in the patients with lung adenocarcinoma. The predicative AUC values based on the radiomic analyses regarding the patients who had both pre-surgical node-positive and node-negative in the CT scans were 0.86 from 159 patients [16].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [16][17][18] had reported that the radiomic analyses were capable of predicting the LNM in the patients with lung adenocarcinoma. The predicative AUC values based on the radiomic analyses regarding the patients who had both pre-surgical node-positive and node-negative in the CT scans were 0.86 from 159 patients [16]. For CT-reported N0 adenocarcinoma patients, the predictive AUC values were 0.91 from 492 patients [17] and 0.76 from 153 patients [18] based on the radiomic analyses, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that radiomics features have great potential to be the maker for tumor phenotype (8)(9)(10)(11)(12)(13)(14)(15)(16)(17), and found Adc can be differentiated from Sqc by radiomics (17)(18)(19)(20)(21)(22)(23). However, The data sets of those studies only included Adc and Sqc, that is to say, the accuracy of those models will be affected by other histological subtypes of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Moreover, some studies have shown that radiomics can predict mediastinal involvement after extracting the data of the ROI from the primary tumour instead of the lymph nodes. 13,14 Magnetic resonance imaging…”
Section: Image-based Techniques Computed Tomographymentioning
confidence: 99%